A Retrospective Study of Glomerulonephritis Patterns Among Jordanian Children - Sheyyab, Ahmed; Hamed, Radi (Jordan Medical Journal, 2024)
Background and Aim: Glomerular diseases affecting pediatric patients differ from conditions encountered in adults. Additionally, the pattern of glomerular disease varies in different regions of the world. In the Mediterranean region, data on glomerular diseases in children patients remain sparse. Therefore, we conducted a study to assess glomerulonephritis disease patterns at our institute and assess for recent incidence trends. Methods: A retrospective study conducted at a university affiliated tertiary hospital located in the capital city of Amman. We included native kidney biopsy reports of patients who fulfilled our age criterion of < 15 years old. Results: Our study showed a total of 178 kidney biopsies, of which 71 patient fulfilled our inclusion criteria. The average age of studied patients was 7.6 ± 4.1 years. Our study had more males compared to females, 56% and 44%, respectively. In nephritic syndrome, IgA nephropathy was the most common cause (13%), which was followed by Post-Infectious glomerulonephritis (8%). In children with nephrotic syndrome, MCD was exceedingly more common in male children when compared to females, 14 versus 8 patients, respectively. While FSGS was more common among females compared to males, 5 versus 2 patients, respectively.